1984
DOI: 10.1111/j.1399-3054.1984.tb04569.x
|View full text |Cite
|
Sign up to set email alerts
|

The physiological basis of seed dormancy in Avena fatua III. Action of nitrogenous compounds

Abstract: Sodium nitrate and nitrite (50–100 mM) induced germination in three out of four genetically pure dormant lines of Avena fatua L. The sensitivity to these treatments was low immediately ater harvest and increased markedly after six months of dry after‐ripening. The observation that a fourth dormant line failed to respond suggests at least two metabolic blocks may be involved in expression of dormancy. An inhibitor of gibberellin biosynthesis, 2‐chloroethyl trimethylammonium chloride, completely inhibited the do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 23 publications
5
30
0
1
Order By: Relevance
“…Increased sensitivity of intact seeds to dormancy-breaking chemicals was observed during afterripening which confirmed similar trends reported previously (1,2,5,6,9). In addition, the pH-dependence for activity in red rice was shown to diminish as afterripening proceeded.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Increased sensitivity of intact seeds to dormancy-breaking chemicals was observed during afterripening which confirmed similar trends reported previously (1,2,5,6,9). In addition, the pH-dependence for activity in red rice was shown to diminish as afterripening proceeded.…”
Section: Discussionsupporting
confidence: 78%
“…Azide, cyanide, and hydroxylamine are known dormancybreaking agents of seeds (2,3,7,8,10,11,(20)(21)(22)(23). In most cases, only partial germination of a highly viable seed population was observed after chemical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrates and nitrites may promote germination by acting as electron acceptors, thus increasing respiration (Adkins et al 1984). The hypothesis is consistent with the increase in respiration rate which precedes nitrate-induced germination but is not supported by evidence that KNO 3 can promote germination without being metabolically reduced (Hilhorst 1990).…”
Section: Discussionsupporting
confidence: 55%
“…3; Table I). These data are consistent with previous work on other dormancy-breaking compounds that are weak acids (8-11, 13, 21, 28, 30, 31 Increased sensitivity of intact seeds to dormancy-breaking compounds was observed during afterripening (Table II) confirming previous reports (1,2,(9)(10)(11)15). These data suggested that increased hull permeability to applied chemicals may occur during dry-afterripening.…”
Section: Discussionsupporting
confidence: 83%